Flipped Classroom Learning Management Model Used by the Plickers Application - Utaminingsih, Sri; Hardika, Fiki Fandi; Fajrie, Nur; Bintoro, Henry Suryo; Aliriad, Hilmy (MIMBAR PGSD Undiksha, 2024)
Currently, many students are less interested in learning, therefore a more interactive approach method is needed. The purpose of this study is to develop Flipped Classroom learning management assisted by Plickers to improve elementary school students' mathematics learning outcomes. The approach used in the development research is the Bord and Gall design. The study was conducted on elementary school students in grade VI of elementary school. Data collection techniques used questionnaires and tests. The results of the study indicate that the learning management design in Flipped Classroom helps Plickers implement management functions, namely planning curriculum analysis, learning objectives and assessments, developing learning steps, and preparing teaching tools. The learning process is carried out outside and inside the classroom. Evaluation is carried out with Plickers. The results of expert validation obtained an average score of 4.5 with the appropriate category. The results of the effectiveness test showed that the calculated F was 95.366 and the calculated sig was 0.000, so 0.000 <0.05, and the magnitude of the influence of the flipped classroom learning model on learning outcomes was 0.618 or 61.8%. Thus, Flipped Classroom learning management with the help of Plickers assessment is used effectively to improve student learning outcomes.